Revitalizing Palang Pintu Tradition in Betawi Culture: Maintaining Local Identity and Heritage in the Modern Era - Rossi Evita; Everhard Markiano Solissa; Jefriyanto Saud; Rahmi Setiawati; Made Ayu Anggreni; Muta’allim (Journal of Science and Education (JSE), 2026)
This study look into the revival of Palang Pintu tradition as a key cultural practice in Betawi Society, emphasizing on its role in maintaining local heritage and cultural identity in the face of modernizing problems. Palang Pintu, which is a traditional part of Betawi weddings, uses poetry, martial arts (Silat), and religious expression to represent hospitality, strength, and bargaining. However, the rapid growth of Jakarta's metropolitan culture has slowly pushed this practice to the edges, making people worry about how long it will last and how important it is in today's world. Qualitative research was used in this study. Ethnographic observation, interviews with cultural leaders, the arts, linguists, and Betawi society were all used in this study. The findings show that three interrelated strategies have been used to carry out revitalization: boosting cultural education in schools and community-based organizations; integrating Palang Pintu into the tourism and creative industries; and utilizing digital platforms to increase public exposure and facilitate intergenerational transmission. In addition to preserving Betawi cultural identity, these initiatives promote intercultural interaction and aid in the development of more inclusive cultural policies in Indonesia. This study confirms that Palang Pintu serves as a cultural symbol that strengthens social solidarity and collective memory among the Betawi people, going beyond a ritualistic display. The resurgence of this custom in contemporary times illustrates the resilience of local heritage amidst globalization, providing valuable insights for sustainable cultural preservation. To enhance scholarly debate on protecting intangible cultural assets in heterogeneous cultures, future study is advised to investigate revitalization approaches among various ethnic communities.